Potensi ekstrak Solanum betaceum terhadap peningkatan sel spermatogenik pada mencit (Mus musculus) yang dipapar timbal asetat - Nurul Fatimah Susanti; Reny I’tishom; Siti Khaerunnisa (Riset Informasi Kesehatan, 2020)
Background : Flavanoids are antioxidants that can prevent the negative effects caused by lead. The flavonoids contained in the Solanum betaceum extract have the potential to prevent the adverse effects of lead on the reproductive tract of rats because it can prevent oxidative stress. The purpose of this study was to prove the effect of Solanum betaceum extract on spermatogenic cells of mice exposed to lead acetate. The hypothesis in this study is that there is an effect of the administration of Solanum betaceum extract to an increase in the number of spermatogenic cells of mice (Mus musculus) exposed to lead Method : this type of research was a true experimental laboratory (true experimental), the research design uses a randomized posttest only control group design approach. The total sample of 40 heads was divided into 5 groups. Group K-: control group without the provision of lead acetate and Solanum betaceum extract, group K +: group with 75 mg / KgBB of lead acetate for 32 days, group P1: group of treatment with 75 mg / KgBB of lead acetate extract + Solanum betaceum extract for 31 days + group 100 mg / gBB for 35 days, group P2: treatment group with 75 mg / kg lead acetate for 31 days + Solanum betaceum extract 200 mg / KgBB for 35 days, and group P3: treatment group with 75 mg lead acetate KgBB for 31 days + Solanum betaceum extract 400 mg / gBB for 35 days.. Results : The mean ± standard deviation of the highest cell spermatogenic was highest 2107.88±78.70.Conclusion : The administration of Solanum betaceum extract can increase the thickness of the seminiferous tubules epithelium and the diameter of the seminiferous tubules in rats (Mus musculus) which are exposed to lead acetat.